What’s in (a) Label? Neural Origins and Behavioral Manifestations of Identity Avoidance in Language and Cognition - Evelina Leivada (Biolinguistics, 2017)
The present work defends the idea that grammatical categories are not in- trinsic to mergeable items, taking as a departure point Lenneberg’s (1967, 1975) claim that syntactic objects are definable only contextually. It is ar- gued that there are four different strands of inquiry that are of interest when one seeks to build an evolutionarily plausible theory of labels and operation Label: (i) linguistic constraints on adjacent elements of the same type such as Repetition/Identity Avoidance ([*XX]), (ii) data that flout these constraints ([XX]), (iii) disorders that raise questions as to whether the locus of impairment is a categorial feature per se, and (iv) operation Label as a candidate for human uniqueness. After discussing categorial identity through these perspectives, this work first traces the origins and manifesta-tions of Identity Avoidance in language and other domains of human cog-nition, with emphasis on attention orienting. Second, it pro- poses a new processing principle, the Novel Information Bias, that (i) cap- tures linguistic Identity Avoidance based on how the brain decodes types and tokens and (ii) explains the universal fact that generally the existence of adjacent occur-rences of syntactically and/or phonologically identical tokens is severely constrained.